Biomassa e densidade de anelídeos, diplópodes e quilópodes em um Argissolo da Formação Itapecuru - MA submetido a diferentesjiíveis de manejo e cobertura morta - Guterres Junior, Delfim Santana Pinheiro (2003)
With the objective of analysis the influence of interactions between tillage system and mulching use, in the biomass and density of edafic macrofauna of annelids, diplopods and quilopods, and the productivity of crops in an Ultisol of Itapecuru - MA Formation under high index pluviometric conditions. Two experiments were carried out in rainy season, the first with 12 treatments in an factorial design, with 4 replications, involving two variants, mulching quantity and, till levei. The second experiment with 6 treatments in an factorial design, with 4 replications, involving the variant quality mulching in two positions. The results allowed the followings conclusions: 1 - The tillage of soil impact, negative, the biomass and the density of natural population of annelids, diplopods and quilopods; 2 - The guandu' s mulching, and, no till impact positive biomass and density of natural population of annelids, diplopods and quilopods; 3 - Eucaliptos sp. shows extrenity unfavorable to fauna studied; 4 - In Itapecuru Formation conditions, the soil management in no till under dead mulching of Cajanus cajan or Clitoria fairchildiana form a good potion to stimulate positive biomass and density of natural population of annelids, diplopods and quilopods; 5- The investigates of relationships between biomass and density of natural population of annelids, diplopods and quilopods, and aeration capacity and hydraulic conductivity physic's quaüty indicators, is suggest for this work continues